Leczenie w psychiatrycznych oddziałach dziennych w porównaniu z oddziałami całodobowymi w róznych europejskich systemach opieki zdrowotnej--załozenia programu EDEN - Kiejna, Andrzej; Kallert, Thomas W; Rymaszewska, Joanna (Psychiatria polska, 2002)
The paper presents the objectives and design of an ongoing multicenter randomized, controlled trial EDEN (European Day Hospital EvaluatioN). The EDEN-study aims to evaluate the efficacy of acute psychiatric treatment in a day hospital setting in five European centres: Dresden, London, Michalovce, Prague and Wroclaw. The main hypothesis is that day hospital treatment for acute psychiatric patients is as effective as conventional inpatient hospital care. The objectives of the study are to evaluate the viability and effectiveness of day hospitals for acute psychiatric treatment, to identify subgroups of patients with a more or less favourable outcome so that the treatment setting might be specifically applied and to ascertain the cost-effectiveness of day hospital treatment compared to conventional inpatient treatment. The study utilises a Randomised Controlled Trial (RCT) design with repeated measures at a maximum of six time points: at admission (t1), one week after admission (t2), four weeks after admission (t3), discharge (t4), three months after discharge (t5), and 12 months after discharge (t6). A combination of well-established standardised assessment instruments and open questions is used in 6 time periods. If the findings accept the main hypothesis of the study, some practical consequences could be inevitable: at a mental health policy level, these results could lead to an increase in the capacity of day hospitals; at the clinical level clinicians could redefine their concepts of care to consider the day hospital as an alternative to conventional inpatient treatment; from economic point of view could lead to reduction of treatment costs.
Keywords: Randomized Controlled Trials as Topic; Germany; Polsko; duševní poruchy; London; Multicenter Studies as Topic; časové faktory; Outcome and Process Assessment, Health Care; Slovakia; Time Factors; lidé; Inpatients; denní péče o pacienty; Německo; Londýn; Humans; poskytování zdravotní péče; Delivery of Health Care; ústavy pro duševně nemocné; multicentrické studie jako téma; Czech Republic; Hospitals, Psychiatric; randomizované kontrolované studie jako téma; Česká republika; Mental Disorders; Slovenská republika; Poland; výsledky a postupy - zhodnocení (zdravotní péče); hospitalizovaní pacienti; Day Care, Medical